Analisis Efisiensi Pemasaran Usaha Budidaya Jamur Tiram Putih di Kota Mataram - FR, Aeko Fria Utama; Nursan, Muhammad; Rakhman, Amry (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
One of the factors that can influence the success of the mushroom business can be seen from the marketing channels and marketing efficiency of the oyster mushroom cultivation business. This research aims to analyze channel profits and marketing efficiency of white oyster mushroom cultivation businesses in Mataram City. The method used in this research is a descriptive method, collecting data obtained using survey and interview techniques. The unit of analysis is the oyster mushroom cultivation business in Mataram City. The determination of the area in this study was determined by "purposive sampling" in Mataram City. The determination of respondents was carried out by census, meanwhile. The data analysis used is marketing channel analysis and marketing efficiency. The research results show that the average profit obtained is IDR. 12,790,868 per area of cultivated land, during one production process. The marketing channel for white oyster mushrooms in Mataram City consists of two channels, channel I is a direct marketing channel, namely producers directly to final consumers and marketing channel II, namely farmers - retailers - final consumers. The marketing channel for white oyster mushrooms in Mataram City is considered efficient, because the producer share value in marketing channel I is 100% and marketing channel II is 80% with a marketing margin of Rp. 5,000/Kg so that marketing channels I and II are said to be efficient because they are greater than 60%